Pertanggung Jawaban Hukum Terhadap Penimbunan Minyak Solar Dalam Mengantisipasi Kenaikan Harga Bahan Bakar Minyak Berdasarkan Undang-Undang Nomor 22 Tahun 2001 Tentang Minyak Dan Gas Bumi (Studi Kasus Putusan Nomor 113/Pid.B/Lh/2022/Pn Kwg - Sihombing, Juan Carlos Adiyaksa; Noor, Aslan (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research is based on the background that Oil and Natural Gas (Migas) play a crucial role in people's lives and the national economy. Regulated by the NRI Law of 1945, Article 33 paragraph (3), Law no. 22 of 2001 regulates oil and gas, including fuel oil (BBM) resulting from processing crude oil. Abuse such as illegal fuel hoarding often occurs, causing shortages and price increases and harming the community. Law enforcement and overcoming crime still requires serious attention from all relevant parties. The research approach used in this research is qualitative research with prescriptive and narrative data analysis. Prescriptive analytical and descriptive analytical in nature, this research is a normative juridical type, considering statutory regulations. Data collection involves library materials, including primary, secondary and tertiary legal materials, with qualitative data analysis methods. The research results are normative qualitative, examining regulations, court decisions and legal views of experts. The application of law regarding criminal acts of hoarding and transporting diesel oil in Indonesia aims to maintain public order, using criminal law in accordance with Law no. 22 of 2001. Cases of hoarding subsidized fuel often involve the perpetrator's intention to seek instant profit by exploiting economic factors. In law enforcement, the element of "abusing the transportation and/or trading of government-subsidized fuel oil" can be charged with a crime in accordance with applicable regulations, such as the case of transporting subsidized diesel oil without a permit which resulted in the defendant being declared guilty Keyword : Oil and Gas, Illegal Actions, Legal Interests